2012
DOI: 10.1177/1073191112446654
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Five Facets Mindfulness Questionnaire (FFMQ) in a Meditating and a Non-meditating Sample

Abstract: The factor structure, internal consistency, construct validity, and predictive validity of the Dutch version of the Five Facet Mindfulness Questionnaire (FFMQ-NL) were studied in a sample of meditators (n = 288) and nonmeditators (n = 451). A five-factor structure was demonstrated in both samples, and the FFMQ-NL and its subscales were shown to have good internal consistencies. Meditators scored higher on all facets of the FFMQ-NL than the participants in the nonmeditating sample. For both samples, expected ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
176
9
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(224 citation statements)
references
References 54 publications
30
176
9
9
Order By: Relevance
“…The NAS highly correlated with mindfulness facets, especially in the sample with meditative experience. Lower convergence between mindfulness-related variables in nonmeditative samples has also been reported before (e.g., de Bruin et al 2012), with observing the most problematic facet because of its erratic association with other mindfulness constructs in samples without meditative experience (e.g., Baer et al 2008;Soler et al 2014a). In the present study, the correlation between observing and the NAS was also the lowest (in both samples) among FFMQ facets.…”
Section: Discussionsupporting
confidence: 59%
“…The NAS highly correlated with mindfulness facets, especially in the sample with meditative experience. Lower convergence between mindfulness-related variables in nonmeditative samples has also been reported before (e.g., de Bruin et al 2012), with observing the most problematic facet because of its erratic association with other mindfulness constructs in samples without meditative experience (e.g., Baer et al 2008;Soler et al 2014a). In the present study, the correlation between observing and the NAS was also the lowest (in both samples) among FFMQ facets.…”
Section: Discussionsupporting
confidence: 59%
“…Debrion, Taper, Masenz, Bogelz, and Comfemis (2012) also showed that mindfulness-based cognitive therapy reduces worry and rumination. This finding was confirmed by Fisk et al (2012), andDe Bruin et al (2012). On the other hand Gerlach et al (2003) showed that social anxiety has severe negative effects on the psychological, personal, and social health of the patients.…”
supporting
confidence: 79%
“…Embora este seja um estudo transversal, não permitindo inferências sobre relações de causalidade, as diferenças observadas vão ao encontro de outros estudos que utilizaram uma metodologia semelhante (de Bruin et al, 2012;Soler et al, 2014). Entendese que a convergência destes resultados transversais remete a duas hipóteses: 1. as pessoas que meditam compartilham características comuns independente da prática propriamente dita (podendo até mesmo procurar este tipo de prática em função destas características); ou 2. a prática de meditação de fato contribui para aumentar os níveis de mindfulness e reduzir o estilo cognitivo de ruminação.…”
Section: Discussionunclassified
“…Dessa forma, esses resultados apoiam estudos que encontraram uma relação inversa entre mindfulness e ruminação tanto em meditadores (Brown & Ryan, 2003;Chambers et al, 2008;de Bruin et al, 2012;Nyklíček & Kuijpers, 2008), como não meditadores (de Bruin et al, 2012;Kiken & Shook, 2014;Paul et al, 2013), sugerindo que há uma interdependência destes padrões mentais para o funcionamento psicológico, e que esta interdependência pode ser especialmente trabalhada no contexto da meditação.…”
Section: Discussionunclassified
See 1 more Smart Citation